The Essentials of Writing: Ten Core Concepts, 2nd Edition - Robert Yagelski (Cengage Learning, 2017)
THE ESSENTIALS OF WRITING: TEN CORE CONCEPTS is a brief writing guide that teaches you ten core concepts you need to learn to become a sophisticated writer. It also offers you practical advice about analytical and argumentative writing, developing an academic writing style, synthesizing ideas, designing documents, conducting research, and evaluating and documenting sources.